Anti-nociceptive and Anti-inflammatory Activities of Crotalaria pallida Aiton (Fam: Fabaceae) Leaves (Bangladesh Pharmaceutical Journal, 2018)
The present study was designed to evaluate the anti-nociceptive and anti-inflammatory properties of the ethanolic extract of Crotalaria pallida Aiton (Family: Fabaceae) leaves based on its traditional uses in the treatment of urinary disorders, external application as a poultice to treat painful swelling of joints and to reduce fever. The anti-nociceptive effect was assessed in mice using acetic acidinduced writhing, formalin-induced paw licking and tail immersion assays. Anti-inflammatory activity was evaluated by carrageenan induced paw oedema in rats. In acetic acid-induced writhing test, the extract at different doses (50 mg/kg and 100 mg/kg bw) significantly (p